Why Don’t Local Governments Buy Catastrophe Insurance? Biased Decision-Makers - Magdalena Anna Swacha-Lech; Mateusz Gawin (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2022)
Theoretical background: Incorporating behavioral analysis into finance allows for finding responses to many questions that researchers have not been able to answer by relying on assumptions characteristic of the traditional, normative approach. One of the areas where recently the achievements of behavioral finance have been used to analyze selected problems is public finance. In this article, we use the achievements of psychology, incorporating them into public finance, which allows us to shed new light on decisions made by public managers in Poland.